Biomarkers for Early Stages of Johne’s Disease Infection and Immunization in Goats - Berry, Aubrey; Wu, Chia-wei; Venturino, Amanda J.; Talaat, Adel M. (Frontiers in Microbiology, 2018)
Background:Mycobacterium avium subsp. paratuberculosis (M. paratuberculosis) is the causative agent of Johne’s disease, a chronic enteric infection of ruminants. Infection occurs within the first few months of life but remains subclinical for an average of 2–5 years. Current diagnostics to detect early subclinical infections lack diagnostic sensitivity, which hinders disease control resulting in significant economic losses to the dairy industry worldwide. The pathophysiology of early infection with M. paratuberculosis is still not well understood and represents a key hurdle toward the development of better diagnostics. Methods: The present study employed a large-scale RNA-Sequencing technology to better understand early stages of M. paratuberculosis infection and immunization. Specifically, gene expression profiles of peripheral blood mononuclear cells (PBMCs) from infected or vaccinated goats were compared to controls. Results: When compared to the naïve control goats, we identified a large number of transcripts (N = 226, 1018, 1714) that were differentially expressed in the M. paratuberculosis-infected goats, goats vaccinated with live attenuated or inactivated vaccines. There were also 1133 differentially expressed (DE) transcripts between vaccinated goats and infected ones. Bioinformatics evaluation of the DE genes indicated the regulation of a large number of genes with immunity and inflammatory functions including IL-18BP, IFN-γ, IL-17A, NOS2, LIPG, and IL-22. Interestingly, a large number of goat genes (N = 667) were regulated whether live or inactivated vaccine were used. Some of the regulated genes (e.g., IL-17A, IFN-γ) continued its unique transcriptional profile up to 12 months post-challenge. Conclusion: Overall, transcriptome analysis of infected and/or immunized goats identified potential targets for developing early diagnostics for Johne’s disease and a potential approach to differentiate infected from vaccinated animals. A similar approach could be used to analyze later stages of Johne’s disease or other chronic infections.